The Influence of Brand Awareness and Product Quality on Purchase Intention of Royale Supreme Brand Laminated Paper at CV. Imperial Indopack East Jakarta - Suparman, Suparman; Andayani, Titik (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research determines how much influence brand awareness and product quality have on purchase intention of laminated paper with the Supreme Royale brand at CV. Imperial Indopack, East Jakarta. The research method uses quantitative methods with a sample of 50 respondents. The method is simple random sampling. The results based on the t-test analysis showed that the brand awareness variable (X1) obtained an at-count value of 2.366 > t-table 1.677 or a significance of 0.022 <0.05 and at-table value of product quality variable (X2) and a value of X2 2.437> 1.677 or a significance of 0.001< 0.05. The brand awareness variable has a significant and positive effect partially on the purchase intention variable (Y), and the product quality variable (X2) is partially significant and positive on the purchase intention variable (Y). Meanwhile, the results of the F test show that the independent variables (independent variables), namely brand awareness (X1) and product quality (X2), have a simultaneous influence on the dependent variable (purchase intention) with an F value of 62,678 < F table 3.19 with a significant level of 0.,00 > 0.05 so that Ha is accepted and Ho is rejected. Based on multiple linear regression analysis, the model or equation is Y = 3.605 + 0.447X1 + 0.691X2.